Project ASPIRE: The Development of a Game for Resilience Training. (September 2014) - Procci, Katelyn; Garcia, David R.; Bratta, Christopher; Wong, Christopher; Formanek, Stephanie; Colley, Kara; Montaquila, Julian; Bowers, Clint
The U.S. Marine Corps' OSCAR program teaches resilience skills to warfighters. This paper describes the design and development process of Project ASPIRE, a light-weight, Flash-based game that serves as a practice environment for the skills learned in OSCAR. Rapid, iterative development/usability cycles were used to identify the ways in which the game could be improved. The results of these usability evaluations are discussed, and general recommendations for the design of training games are provided.